2006
DOI: 10.1590/s0001-37652006000300016
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic constraints on the age of the Botucatu Formation in Rio Grande do Sul, southern Brazil

Abstract: Paleomagnetic and rockmagnetic data are reported for the aeolian Botucatu Formation, in the southern Brazilian State of Rio Grande do Sul. Oriented samples were taken from a section located between the cities of Jaguari and Santiago. After thermal and alternating field demagnetization, both normal and reversed characteristic remanent magnetizations were found. These results yielded 13 reversed and 5 normal polarity sites, composing a magnetostratigraphic column displaying a sequence of reversed-normal-reversed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Because of this, and its stratigraphic relationships with the Arapey Formation, an earliest Cretaceous (Berriasian-Hauterivian) age is proposed for the Rivera Member. The paleomagnetic data recently published by Tamrat and Ernesto (2006) for the correlative Botucatu Formation are consistent with this chronological proposal.…”
Section: Commentssupporting
confidence: 86%
“…Because of this, and its stratigraphic relationships with the Arapey Formation, an earliest Cretaceous (Berriasian-Hauterivian) age is proposed for the Rivera Member. The paleomagnetic data recently published by Tamrat and Ernesto (2006) for the correlative Botucatu Formation are consistent with this chronological proposal.…”
Section: Commentssupporting
confidence: 86%
“…with Early Cretaceous poles (160-130 Ma) from South America (Fig. 7, Tamrat & Ernesto 2006). Since the IRM inclination experiments described above indicated that no significant inclination shallowing affects these rocks, two possible interpretations are suggested.…”
Section: N T E R P R E Tat I O N a N D Discussion Smentioning
confidence: 92%
“…There is no difference in both directions of each pole. (C) LC2 (pole from De La Cuesta Formation, Los Colorados Anticline outcrop) and Cretaceous palaeomangetic poles of South America (Besse & Courtillot 2002; Tamrat & Ernesto 2006).…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…The mean of the minimum axes k 3 (the pole to the foliation plane) directions suggest a dip of 24 ∘ to N205 ∘ , and such a bedding correction would displace the APP paleomagnetic pole to a position (157 ∘ E 80 ∘ S), if taken as representative of the entire igneous province. This pole position is close to the Late Jurassic segment of the apparent polar wander path for South America [29], and would imply in a remagnetization of the entire province, for which there isare no evidences from the paleomagnetic and the rockmagnetic data described above. Therefore, if the maximum axes k 1 are re-ally parallel to the flow direction it is possible that the foliation plane refers only to the Pão de Açúcar complex or it means that the emplacement surface was not horizontal.…”
Section: Discussionmentioning
confidence: 59%